The Role of the Jayapura City Border Management Agency in the Jayapura City Sister City Program with Vanimo and Wewak Papua New Guinea - Pugu, Melyana Ratana; Sinaga, Melpayanti (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the role of the Jayapura City Border Management Agency in the Sister City program with Vanimo and Wewak, Papua New Guinea. This program is expected to strengthen bilateral relations and improve the welfare of people in border areas. The research method used is qualitative, with a case study approach, where data are obtained through in-depth interviews with various stakeholders, including government officials, local communities, and non-governmental organizations. Analysis of related documents is also carried out to explore existing policies and programs. The results of the study are expected to show that the Border Management Agency plays an important role in facilitating collaboration between the City of Jayapura and cities in Papua New Guinea. This role includes the development of the economic sector, the promotion of cultural exchanges, and the resolution of security issues arising in the border region. In addition, the study is expected to find that challenges such as lack of infrastructure and lack of accurate information can hinder the effectiveness of the program. The output of this research is in the form of strategic recommendations to increase the effectiveness of the Sister City program, including strengthening communication networks and cooperation between related institutions. Thus, this research is expected to make a significant contribution to the development of policies that support better border management, as well as improve the welfare of the people on both sides. These results can also serve as a reference for further research on inter-city cooperation in border areas.